Global burden of stroke attributable to dietary risk factors in the GBD 2021 study - Xie, Wen; Li, Aiping; Zhang, Yao; Tan, Shenglan; Luo, Juan (Frontiers in Nutrition, 2024)
ObjectiveWe sought to assess the impact of dietary risk on the worldwide burden of stroke, focusing specifically on ischemic stroke.MethodsUtilizing information from the Global Burden of Disease Study 2021 (GBD2021), we evaluated the age-standardized death rate (ASDR), the age-standardized disability-adjusted life years (DALYs) rate, and the age, sex, and regional distribution of the estimated annual percentage change (EAPC) of the stroke burden linked to dietary risk from 1990 to 2021.ResultsThe global overall ASDR and the age-standardized DALY rate per 100,000 population for stroke linked to dietary risk from 1990 to 2021 exhibited a declining trend [EAPC = −1.95; EAPC = −1.70, respectively]. The reduction in ASDR was statistically more pronounced in female (EAPC = −2.42) compared to males (EAPC = −1.60). The dietary factor exerting the most significant impact on stroke in 2021 was a high sodium diet, succeeded by a diet deficient in fruit. The regions and countries most affected by a high-sodium diet on the ASDR for ischemic stroke are Central Europe (9.86 per 100,000 population) and North Macedonia (33.13 per 100,000 population), respectively; the regions and countries with the most substantial influence on the age-standardized DALY rate are East Asia (187.15 per 100,000 population) and North Macedonia (477.26 per 100,000 population). The ASDR and age-standardized DALY rates across 5 Socio-Demographic Index (SDI) regions, 20 regions, and over 170 countries worldwide demonstrated a notable downward trend, with the regions experiencing the most significant decline being High SDI (EAPC: −3.64; EAPC: −2.74, respectively). The sole increase in ASDR was recorded in southern sub-Saharan Africa.ConclusionThe worldwide toll of stroke linked to dietary risks may have diminished from 1990 to 2021. Nevertheless, the most significant dietary contributors are diets rich in sodium and deficient in fruit, with the stroke burden associated with dietary risks remaining especially elevated in Central Europe, East Asia, and Eastern Europe. Lowering sodium consumption and enhancing fruit intake can aid in alleviating the global disease burden.